The Effect of Neck Massage on Expenditure of Breast Milk in Post Partum Mom - Parida Hanum; Sarah Yosephine Pardede; Setia Anggreani (Global Health Science Group, 2020)
The anxiety experienced by Post Partum mothers when breastfeeding their babies makes mothers avoid and refuse to give breast milk to their babies, will have an impact on the lack of suction in the babies and will affect the lack of milk production so that the milk is not smooth. Breast milk production will continue to increase for 6 months with an average production of 700 - 800 ml then milk production will decrease after more than the first 6 months to 500 - 600 ml. One method that can stimulate milk production is the neck massage method. The purpose of this study was to determine the effect of nape massase on breastfeeding in post partum mothers at the Matapao Juliana Tanjung Clinic. The research design used a pre-experimental method with one group pre-test and post-test design. The number of samples in this study were 25 people based on the total population of mothers breastfeeding infants aged> 6 months with total sampling technique. Aspects of data measurement using observation sheets with bivariate analysis. The results of this study indicate that the respondents experienced an increase in breast milk production. The results of data analysis showed that the value of Z = 4.375b and the value of p-value = 0.000 with a significant level of p <0.005. The conclusion of this study states that there is an effect of cervical massase on breastfeeding in mothers.